Early preclinical plasma protein biomarkers of brain trauma are influenced by early seizures and levetiracetam - Patricia G. Saletti; Wenzhu B. Mowrey; Wei Liu; Qianyun Li; Jesse McCullough; Roxanne Aniceto; I‐Hsuan Lin; Michael Eklund; Pablo M. Casillas‐Espinosa; Idrish Ali; Cesar Santana‐Gomez; Lisa Coles; et al. (Epilepsia Open, 2023)
Abstract Objective We used the lateral fluid percussion injury (LFPI) model of moderate‐to‐severe traumatic brain injury (TBI) to identify early plasma biomarkers predicting injury, early post‐traumatic seizures or neuromotor functional recovery (neuroscores), considering the effect of levetiracetam, which is commonly given after severe TBI. Methods Adult male Sprague–Dawley rats underwent left parietal LFPI, received levetiracetam (200 mg/kg bolus, 200 mg/kg/day subcutaneously for 7 days [7d]) or vehicle post‐LFPI, and were continuously video‐EEG recorded (n = 14/group). Sham (craniotomy only, n = 6), and naïve controls (n = 10) were also used. Neuroscores and plasma collection were done at 2d or 7d post‐LFPI or equivalent timepoints in sham/naïve. Plasma protein biomarker levels were determined by reverse phase protein microarray and classified according to injury severity (LFPI vs. sham/control), levetiracetam treatment, early seizures, and 2d‐to‐7d neuroscore recovery, using machine learning. Results Low 2d plasma levels of Thr231‐phosphorylated tau protein (pTAU‐Thr231) and S100B combined (ROC AUC = 0.7790) predicted prior craniotomy surgery (diagnostic biomarker). Levetiracetam‐treated LFPI rats were differentiated from vehicle treated by the 2d‐HMGB1, 2d‐pTAU‐Thr231, and 2d‐UCHL1 plasma levels combined (ROC AUC = 0.9394) (pharmacodynamic biomarker). Levetiracetam prevented the seizure effects on two biomarkers that predicted early seizures only among vehicle‐treated LFPI rats: pTAU‐Thr231 (ROC AUC = 1) and UCHL1 (ROC AUC = 0.8333) (prognostic biomarker of early seizures among vehicle‐treated LFPI rats). Levetiracetam‐resistant early seizures were predicted by high 2d‐IFNγ plasma levels (ROC AUC = 0.8750) (response biomarker). 2d‐to‐7d neuroscore recovery was best predicted by higher 2d‐S100B, lower 2d‐HMGB1, and 2d‐to‐7d increase in HMGB1 or decrease in TNF (P < 0.05) (prognostic biomarkers). Significance Antiseizure medications and early seizures need to be considered in the interpretation of early post‐traumatic biomarkers.